Hybrid Micro-Enterprises – Founding Motives and the Meaning of Success - Bicho, M.; Nikolaeva, R.; Lages, C.; Ferreira, F. (European Academy of Management Conference, 2017)
This research explores hybrid micro-entrepreneurs’ founding motivations and their transformations into visions of success. We conduct two studies – one exploring the founding motivations and a second one the perceptions of success – taking the managers’ point of view in the context of hybrid enterprises pursuing both economic and non-economic goals. We find that entrepreneurs are driven mostly by non-economic goals, which are later reflected in their vision of success. To build the evaluation framework we applied a multiple-criteria decision analysis with a practical application of deriving participants’ scores. The success framework consists of seven indicators: training, professional development, marketing, management, external factors, infra-structures and organizational aspects. Human capital factors are perceived as the most important for success – translating the professional motivations for founding. Reversely, external factors, which are usually considered crucial to attain legitimacy and longevity, are perceived the least important factors. Given the findings, are hybrid micro-entrepreneurs ready to succeed?